Desain Penyiram Tanaman Otomatis Berbasis Arduino Menggunakan Sensor Kelembaban Tanah - Yoli Andi Rozzi; Jhoanne Fredricka; Kelik Sussolaikah (STMIK Budi Darma, 2023)
In line with the development of an increasingly advanced era, humans also expect a tool or technology that can help and facilitate in carrying out daily work. The technology developed varies according to the desired field. Both in the fields of education, communication, health and even in the fields of agriculture and food. One application of technology that can meet human needs in the field of food and agriculture is an automatic plant watering system. This system is designed to replace manual work to become automatic when watering plants. The expected benefit of this system is that the system can facilitate human work in watering plants so that it is more effective and efficient. This system consists of a Soil Moisture Sensor, Arduino Uno Microcontroller, Riley Driver, Pompa Air and LCD. The Soil Moisture Sensor system will be used to detect soil moisture. After reading the soil moisture value, the data will be sent to Arduino Uno, then Arduino will give an order to turn on/off the relay driver. Then the Relay Driver will set the conditions so that the pump can automatically water the water according to the needs of the plants. The results of this study indicate that the system works well, where the readable data will be displayed on the LCD. The automatic plant sprinkler system can work well to automatically water the plants when the soil moisture reading is below 60%